STUDI PENGARUH MEDAN MAGNET TERHADAP JUMLAH SEL DARAH MERAH (ERITROSIT) PADA TIKUS PUTIH (RATTUSNPRVEGICUS) - Indra Sukma Sari Kusuma, A A A; Trisnawati, Ni Luh Putu; Artawan, I Nengah (BULETIN FISIKA; Vol 15 No 1 (2014): BULETIN FISIKA, 2014)
The research on the influence of magnetic field on the number of erythrocytes in the rat (Rattusnorvegicus) had done. The study was conducted using Rats aged approximately three months with a body weight between 150 gr-300 grinterval. Rats were given exposure to magnetic fields varying from 1830 gauss to 5220 gauss interval by using500 and 500 gauss to 3500 gauss interval by using765 for 6 hours in 3 days. The research has been showed there some data are the above result specially on the decrease of erythrocytes number. And other some data that has increased. The above result speciallyon the decrease of erythrocytes number presumably the composition of it dominated by elements iron (Fe) were classified as ferromagnetic and non-linear are caused. On the recovery time has been set the white rat data showed some recovery time close to 5 days, more than 5 days.